Context counts: Investigating pain management interventions in HIV-positive men living in a rural area - Cameron Reardon; Antonia Wadley; Romy Parker (African Journal of Primary Health Care & Family Medicine, 2023)
Background: Pain remains a prevalent and burdensome complaint for people living with human immunodeficiency virus and/or aquired immunodeficiency syndrome (LWHA). Positive Living (PL), a multimodal pain intervention, reduced pain in female South Africans LWHA. We investigated the efficacy of the PL programme in South African males living with human immunodeficiency virus and/or acquired immunodeficiency syndrome (MLWA) in a rural community.